Using a Textual Prompt to Teach Multiword Requesting to Two Children With Autism Spectrum Disorder. Issue 6 (November 2019) - Roche, Laura; Carnett, Amarie; Sigafoos, Jeff; Stevens, Michelle; O'Reilly, Mark F.; Lancioni, Giulio E.; Marschik, Peter B.
Autism spectrum disorder is characterized by social and communication impairment, but some children appear to have relative strength in areas such as reading printed words. The present study involved two children with limited expressive communication skills, but relatively stronger reading ability. Based on this existing strength, we evaluated a textual prompting procedure for teaching the children to produce multiword spoken requests. The effect of providing textual prompts on production of multiword requests was evaluated in an ABAB design. The results showed that multiword requests increased when textual prompts were provided and decreased when the prompts were removed. In subsequent phases, the textual prompts were successfully faded by gradually making the printed text lighter and lighter until eventually the prompts were eliminated altogether. We conclude that identification of children's strengths may assist in identifying effective prompting procedures that could then be used in teaching functional communication skills.